An Irshad-Based Approach in the Digital Age Through the Dhikr Practices of Habib Luthfi bin Yahya - Yumna Azkia; Nur Asia Tawang; Vedat Karadeniz; Moch Zainal Arifin Hasan; Sinawar Sinawar (Al Irsyad, 2025)
Habib Luthfi bin Yahya’s use of digital technology in disseminating dzikir has expanded the reach of Islamic preaching, created virtual spiritual communities, and strengthened religious interactions in an interactive and trustworthy manner. This study analyzes Habib Luthfi bin Yahya’s utilization of digital media to spread dzikir and provide spiritual guidance to the broader public in an engaging and interactive way. The research employs a qualitative approach and literature review, collecting data through documentation from various books, journals, and relevant online articles. The findings reveal that: preaching strategies in the digital era require adjustments in methods, content, and media to align with technological advancements and the realities of modern society. The irsyad approach, emphasizing personal relationships between mentors and mentees, is effective in addressing individual psychological and spiritual issues. Dzikirtherapy, as a method of da'wah and spiritual healing, helps foster inner peace and closeness to God. Habib Luthfi bin Yahya serves as a model of a moderate scholar who wisely and broadly uses digital media to convey peaceful and comforting Islamic messages. Through online platforms, he has successfully built a spiritual community and raised religious awareness across generations and regions. Conclusion: Digital technology is effective for Islamic preaching; scholars like Habib Luthfi spread Islam widely and profoundly through digital platforms.